Saliva as a tool for monitoring steroid, peptide and immune markers in sport and exercise science - Papacosta, E.; Nassis, G. P. (Journal of Science and Medicine in Sport, 2011)
Objectives: This paper discusses the use of saliva analysis as a tool for monitoring steroid, peptide, and immune markers of sports training. Design: Salivary gland physiology, regarding the regulation and stimulation of saliva secretion, as well as methodological issues including saliva collection, storage and analysis are addressed in this paper. The effects of exercise on saliva composition are then considered. Method: Exercise elicits changes in salivary levels of steroid hormones, immunoglobulins, antimicrobial proteins and enzymes. Cortisol, testosterone and dehydroepiandrosterone can be assessed in saliva, providing a non-invasive option to assess the catabolic and anabolic effects of exercise. Validation studies using blood and salivary measures of steroid hormones are addressed in this paper. Effects of acute exercise and training on salivary immunoglobulins (SIgA, SIgM, SIgG) and salivary antimicrobial proteins, including alpha-amylase, lysozyme and lactoferrin, are also discussed. Results: Analysis of cortisol and testosterone in saliva may help detect the onset of non-functional overreaching and subsequently may help to prevent the development of overtraining syndrome. Assessment of salivary immunoglobulins and antimicrobial proteins has been shown to successfully represent the effects of exercise on mucosal immunity. Increases in SIgA and antimicrobial proteins concentration and/or secretion rate are associated with acute exercise whereas conversely, decreases have been reported in athletes over a training season leaving the athlete susceptible for upper respiratory tract infections. Conclusions: The measurement of physiological biomarkers in whole saliva can provide a significant tool for assessing the immunological and endocrinological status associated with exercise and training.